A computer-mediated interface for jazz piano comping - Dias, R. (2016)
This paper presents a dynamic interface and voicing algo- rithm for real-time performance of jazz piano comping. Starting with a given song with a predefined harmonic progression, the algorithm calculates and maps an array of chord voicings to a virtual piano keyboard that can be played in real-time with any physical multi-touch input device like an iPad or computer keyboard. By taking care of the note selection for the voicings, the interface pro- vides a simplified and intuitive way to play sophisticated voicings, while leaving the control over the performance aspects like timing, register, wideness and density to the user.